Optimization of staged combustion in a 600 MWe tangentially fired boiler with wall air injection. (1st September 2020) - Pei, Jianjun; Wang, Haiming; You, Changfu
Highlights: Wall air injection can optimize the low NOx combustion in the main combustion zone. The airspeed, temperature and CO concentration near the water wall were reduced. The airflow rotation was enhanced and the temperature in furnace center increased. The wall air velocity of 40 m/s with the clockwise injection direction is optimum. Abstract: Low NOx combustion technology is used in coal-fired boilers to reduce the generation of NOx cost-effectively. However, this technology causes the problem of high temperature corrosion and slagging of water-cooled walls. In this study, a wall air injection technique is presented to effectively alleviate these problems, especially for the low quality coal. The wall air is injected vetically into the furnace to reduce the tangential circle diameter through the nozzles installed on the water wall. In a 600 MWe tangentially fired boiler, the wall air injection technique was retrofitted to study the influences of the wall air velocity and the tangential circle direction on the boiler combustion performance by simulation method. The applicability of the wall air injection technique for the combustion of the design coal and the low quality coal was also studied. The results showed that the wall air velocity of ~ 40 m/s was optimum for the combustion of the low quality coal. The following improvements in the combustion performance were observed at the wall air velocity of 40 m/s: 1) the actual tangential circle diameter was close to the design value of 14 m; 2) the mean flue gas temperature on the water wall decreased by about 600 K while that in the furnace center increased by about 80 K at most; 3) the mean CO mole fraction reduced by about 0.03; and 4) the NOx generation reduced by 38 mg/Nm 3 . When the wall air injection direction was clockwise, the NOx generation at furnace outlet decreased by 6 mg/Nm 3 .